1989
DOI: 10.1111/j.1365-2621.1989.tb05989.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Myoinositol Phosphate Esters on In Vitro and In Vivo Digestion of Protein

Abstract: Effects of phytate and its hydrolysis products (myo-inositol phophate esters) on protein digestion were investigated by in vitro and in viva procedures. Tri-, tetra-, penta-, and hexa-phosphate ester fractions, isolated from phytate hydrolysates, inhibited pepsin digestion of casein and bovine serum albumin in vitro. The inhibition ranged from 0% for the mono-and diphosphate esters to 9-14% with the hexdphosphate ester (phytate). The phosphate ester fractions did not significantly affect trypsin digestion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…These results are in agreement with in vitro studies that phytate significantly inhibited the peptic or tryptic digestion of proteins (Singh and Krikorian 1982;Knuckles et al 1985Knuckles et al , 1989Vaintraub and Bulmaga 1991;Caldwell 1992). However, limited in vivo research has been conducted in this area.…”
Section: Archives Of Animal Nutrition 299supporting
confidence: 94%
“…These results are in agreement with in vitro studies that phytate significantly inhibited the peptic or tryptic digestion of proteins (Singh and Krikorian 1982;Knuckles et al 1985Knuckles et al , 1989Vaintraub and Bulmaga 1991;Caldwell 1992). However, limited in vivo research has been conducted in this area.…”
Section: Archives Of Animal Nutrition 299supporting
confidence: 94%
“…However, this was not reflected in vivo (162). It was later found that the presence of phytate inhibits the digestion of proteins and does not affect the hydrolysis of low molecular weight substrates (163).…”
Section: Effects On Enzyme Activitiesmentioning
confidence: 92%
“…This initial, rapid step is followed by a progressive protein-protein aggregation that may result in precipitation (Rajendran and Prakash, 1993). The crucial proposition is that phytate-bound protein is refractory to pepsin digestion (Camus and Laporte, 1976;Knuckles et al, 1985Knuckles et al, , 1989. Camus and Laporte (1976) attributed inhibition of pepsin digestion by phytate to the formation of insoluble protein-phytate complexes under acidic conditions.…”
Section: Underlying Mechanismsmentioning
confidence: 99%